SegaSoft Networks : multi-player online gaming - Glazer, Rashi; Ba, Mbissane; Frizelle, Charles; Iyer, Amaresh; Pearson, Rich (London : SAGE Publications Ltd, 2017)
SegaSoft, a software development company needed to decide whether the company should focus on being a software development company, online gaming aggregator of third party titles, or both. In September 1997, SegaSoft had entered into the online gaming industry. Prior to September, SegaSoft had established itself as a software development company dedicated to the development of interactive titles for PCs, gaming consoles, and the Internet. Students will discuss whether SegaSoft should utilize its assets to position its online component, reinforce its apparent core competency of software development, or attempt to support both software development and Internet gaming. Was there an opportunity to exploit the brand identity of its parent company, and if so, which of the above strategies would it most benefit? How could the company maximize its online component to maximize its revenue stream in light of its current consumer base and an unproven revenue model?
Originally published in Glazer, R., Ba, M., Frizelle, C., Iyer, A., & Perason, R. (2007). The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business.
Description based on XML content.
Keywords: elektronické knihy; electronic books; SegaSoft (Firm); Strategic planning; Product management; Computer software -- Development